2011
DOI: 10.1210/jc.2011-1251
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Fructose and High Fructose Corn Syrup Increase Postprandial Triglycerides, LDL-Cholesterol, and Apolipoprotein-B in Young Men and Women

Abstract: Consumption of HFCS-sweetened beverages for 2 wk at 25% E increased risk factors for cardiovascular disease comparably with fructose and more than glucose in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
160
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(183 citation statements)
references
References 38 publications
11
160
4
1
Order By: Relevance
“…We also take above concerns into account, the hematology results were in normal range in adult monkeys [63]. Several articles report that triglycerides level were increased as the consequences of ingesting sugar-sweetened beverage [30][31][32]61], in our study, triglycerides level increased significantly after 1 year of beverage intake. Studies indicate that fructose consumption and have been associated with fatty liver [64,65] and hepatic fibrosis [66] in people, higher exposures to dietary fructose result in the development of hepatic lipidosis in nonhuman primates when consumed ad libitum for periods equivalent to ≥ 1 human year and ALT, AST, GGT increased after 6 weeks of high fructose diet exposure [67], the detected biomarkers (NEFA, TCHO, ALT, AST, GGT in Tables 3 and 4) changing trend in our study also reveal this possibility.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…We also take above concerns into account, the hematology results were in normal range in adult monkeys [63]. Several articles report that triglycerides level were increased as the consequences of ingesting sugar-sweetened beverage [30][31][32]61], in our study, triglycerides level increased significantly after 1 year of beverage intake. Studies indicate that fructose consumption and have been associated with fatty liver [64,65] and hepatic fibrosis [66] in people, higher exposures to dietary fructose result in the development of hepatic lipidosis in nonhuman primates when consumed ad libitum for periods equivalent to ≥ 1 human year and ALT, AST, GGT increased after 6 weeks of high fructose diet exposure [67], the detected biomarkers (NEFA, TCHO, ALT, AST, GGT in Tables 3 and 4) changing trend in our study also reveal this possibility.…”
Section: Discussionsupporting
confidence: 58%
“…Recently several articles report that the consumption of fructose sweetened beverages increases visceral adipose deposition and triglycerides levels [30,31], produces dyslipidemia, and decreases glucose tolerance/insulin sensitivity [32]. HFCS made by enzymatic isomerization of glucose to fructose was introduced as HFCS-42 (42% fructose) and HFCS-55 (55% fructose) in 1967 and 1977, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The higher carbohydrate diet employed in the Women's Health Initiative had no effect on either triglycerides or high density lipoprotein [42]. Some investigators have suggested that added sugars may increase abnormalities by raising low density lipoprotein (LDL) [43] [44], although research in our laboratory has yielded no change in either LDL or total cholesterol [34] [45].…”
Section: Discussionmentioning
confidence: 87%
“…However, HFCS intake may promote the development of chronic diseases, such as diabetes and cardiovascular disease 11 , which have been related to hypertriglyceridemia 12 and insulin resistance 13 in patients with prolonged HFCS intake.…”
Section: Introductionmentioning
confidence: 99%